Participatory research in south africa’s socio-economic impact assessment systems (seias) - Mokone, Plantina Tsholofelo (University of the Witswatersrand, Johannesburg, 2022)
PR is an integral part of the SEIAS methodology. When applied completely and effectively, it can expand the range of alternatives created for decision-making by allowing policymakers to document and interpret a policy challenge with those affected most. 2 PR promotes close collaboration between policymakers and the participants— traditionally considered the ‘subjects’ of a study. PR allows them to establish a research agenda, collect data, conduct critical analysis, and devise activities to achieve social change. According to Booysen (2007:172), participation in public policy (PP) decision-making is crucial. This involvement affords people and groups a ‘transformational voice’, enabling them to affect outcomes. This reasoning has severe implications for the ideals of democracy (Booysen, 2007
This research is submitted in partial fulfillment of the requirement in Masters in management in Public Policy at the Wits School of Governance
Keywords: Participatory research; South africa; Socio-economic impact assessment systems (seias); UCTD; SDG-8: Decent work and economic growth